Pengaruh Durasi Iskemia terhadap Ekspresi Protein P53 Otak Tikus Pasca Transient Bilateral Common Carotid Artery Occlusion (TBCCAO) - Ety Sari Handayani; Kuswati Kuswati; Zainuri Sabta Nugaha; Nurul Hidayah; Nesti Herennadia; Gea Sonia Amanda; Salsabila Ajeng (EKSAKTA: Journal of Sciences and Data Analysis, 2019)
Tumor suppressor gene p53 is one of the specific parameters of the occurrence of brain neuron death in animal models of brain ischemia. Several studies show that the duration of reperfusion of tBCCAO has an effect on the expression of p53 protein. The duration of ischemia for 5 minutes followed by reperfusion of 1 hour, 4 hours, 8 hours, 24 hours, and 7 days increased the expression of p53 protein. 30-minute ischemia induction followed by 4-hour reperfusion showed increased p53 protein expression in rat serum. It is not yet known how the influence of tBCCAO ischemia duration on p53 expression in rat brain. This study used Wistar, male rats, aged 3-4 months, weighing 175-250 gr, and healthy. Group A was a group of tBCCAO rats with a duration of 5 minutes ischemia, 24-hour reperfusion duration (five). Group B was a group of tBCCAO mice with a duration of 10 minutes ischemia, 24-hour reperfusion (five). Group C is a group of sham operated mice (five). The expression of p53 protein is semi quantification of p53 expressed on pyramidal neuron of the frontal brain (Cortex Prefrontalis, striatum) and CA1 hippocampus, with IHC staining using anti-p53 antibodies. P53 expression will be seen in the cytoplasm of pyramidal neuron CA1 hippocampus. Cytoplasm of neurons will be brownish in color. The semi-quantification method of p53 expression uses the ALLRED score. Data analysis using one way ANOVA test. The analysis found differences in frontal brain p53 expression (cortex prefrontalis and striatum) (p = 0.00) and there were differences in p53 expression in pyramidal neuron CA1 hippocampal (p = 0.013). There was an effect of the duration of tBCCAO on expression of p53 protein in rat brain after 24-hour reperfusion. Keywords: tBCCAO’s duration, p53, rat’s brain